PENERAPAN METODE NILAI HASIL PADA PROYEK PEMBANGUNAN GEDUNG PELAYANAN BPKB DIT LANTAS POLDA MALUKU - Julia Dewi Leatemia; Lenora Leuhery; Nelda Maelissa (Journal Agregate, 2022)
The construction of the BPKB Service Building of the Maluku Police Traffic Directorate is planned to be completed in 150 calendar days. But in fact the project experienced addendum 1 on November 2, 2020 because at the time of the field inspection the size of the plan drawing did not match the size in the field, so this project experienced a delay of 27.895%. So that delays in project implementation do not recur, the author's goal is to find out cost and time deviations using the result value method. This method uses basic assumptions to make forecasts so that you have enough time to think about how to deal with problems in the future. Data collection techniques carried out are site surveys, observations, and literature. There are two types of variables, namely the independent variable is time and the dependent variable is cost. The data analysis technique used the result value method. The results of the analysis at week 28 of the cost performance index (CPI) < 1 which means the actual costs (ACWP) incurred are greater than the planned work costs (BCWP) so that the project experiences a cost deviation of Rp. 106,014.970.36 from the value a contract of Rp. 21,701,579,200.00 with a percentage of 0.49% and a time performance index (SPI) < 1 which means the project performance is slower than the planned schedule so that the project experiences time deviations for 200 working days with a weight of 6.5845% from the planning schedule 150 working days. Keywords : Earned Value Method, Schedule Performance Index (SPI), Cost Performance Index (CPI)